Dopamine D3 receptor Ser9Gly variant is associated with impulse control disorders in Parkinson's disease patients. (September 2016) - Krishnamoorthy, Soumya; Rajan, Roopa; Banerjee, Moinak; Kumar, Hardeep; Sarma, Gangadhara; Krishnan, Syam; Sarma, Sankara; Kishore, Asha
Abstract: Introduction: Impulse control disorders (ICD) are reported to occur at variable frequencies in different ethnic groups. Genetic vulnerability is suspected to underlie the individual risk for ICD. We investigated whether the allelic variants of dopamine (DRD3), glutamate (GRIN2B) and serotonin (HTR2A) receptors are linked to ICD in Indian Parkinson's disease (PD) patients. Methods: We conducted a prospective, case-control study which included PD patients (70 with ICD, 100 without ICD categorized after direct psychiatric interview of patient and caregiver) and 285 healthy controls. Single nucleotide polymorphism (SNP) variants of DRD3 p.S9G (rs6280), GRIN2B c.2664C>T (rs1806201) and HTR2A c.102T>C (rs6313) were genotyped. Results: Multivariate regression analysis revealed that DRD3 p.Ser9Gly (rs6280) heterozygous variant CT (OR = 2.22, 95% CI: 1.03–4.86, p = 0.041), higher daily Levodopa equivalent doses (LED) of drugs (for 100 mg LED, OR = 1.14, 95% CI: 1.01–1.29, p = 0.041), current dopamine agonist but not Levodopa use (OR = 2.16, 95% CI: 1.03–4.55, p = 0.042) and age of onset of motor symptoms under 50 years (OR 2.09, 95% CI: 1.05–4.18, p = 0.035) were independently associated with ICD. Conclusion: DRD3 p.Ser9Gly (rs6280) CT genotype is associated with ICD in Indian PD patients and this association is novel. Enhanced D3 receptor affinity due to gain-of-function conferred by the glycine residues could impair reward-risk assessment in the mesolimbic system and contribute to development of impulsive behaviour, in carriers of this genotype. Highlights: DRD3 p.Ser9Gly (rs6280) "CT" variant is associated with Impulse Control Disorders in Indian PD patients. This association is novel. It is independent of the clinical factors like age at onset, dopamine agonist use, total daily LED and dopamine agonist LED. Ethnic variations in ICD prevalence may have a genetic basis.